Hyperactivation of Posterior Default Mode Network During Self-Referential Processing in Children at Familial High-Risk for Psychosis - Collin, Guusje; Bauer, Clemens C. C.; Anteraper, Sheeba Arnold; Gabrieli, John D. E.; Molokotos, Elena; Mesholam-Gately, Raquelle; Thermenos, Heidi W.; Seidman, Larry J.; Keshavan, Matcheri S.; Shenton, Martha E.; Whitfield-Gabrieli, Susan (Frontiers in Psychiatry, 2021)
Patients with schizophrenia spectrum disorders show disturbances in self-referential processing and associated neural circuits including the default mode network (DMN). These disturbances may precede the onset of psychosis and may underlie early social and emotional problems. In this study, we examined self-referential processing in a group of children (7 – 12 years) at familial high risk (FHR) for psychosis (N = 17), compared to an age and sex-matched group of healthy control (HC) children (N = 20). The participants were presented with a list of adjectives and asked to indicate whether or not the adjectives described them (self-reference condition) and whether the adjectives described a good or bad trait (semantic condition). Three participants were excluded due to chance-level performance on the semantic task, leaving N = 15 FHR and N = 19 HC for final analysis. Functional MRI (fMRI) was used to measure brain activation during self-referential versus semantic processing. Internalizing and externalizing problems were assessed with the Child Behavior Checklist (CBCL). Evaluating main effects of task (self > semantic) showed activation of medial prefrontal cortex in HC and precuneus/posterior cingulate cortex (PCC) in FHR. Group-comparison yielded significant results for the FHR > HC contrast, showing two clusters of hyperactivation in precuneus/ PCC (p = .004) and anterior cerebellum / temporo-occipital cortex (p = .009). Greater precuneus/PCC activation was found to correlate with greater CBCL internalizing (r = 0.60, p = .032) and total (r = 0.69, p = .009) problems. In all, this study shows hyperactivity of posterior DMN during self-referential processing in pre-adolescent FHR children. This finding posits DMN-related disturbances in self-processing as a developmental brain abnormality associated with familial risk factors that predates not just psychosis, but also the prodromal stage. Moreover, our results suggest that early disturbances in self-referential processing may be related to internalizing problems in at-risk children.